CORAK TAFSIR MAQA - Nisa, Nur Maliyah Nisa Mardiyah; Fa'id, Muhammad Nur Fawaid As'ad (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2025)
Book Nazm al-Durar fi Tanasib al-‘Ayat wa al-Suwar by al-Burhan al-Din ‘Abi alHayan ‘Ibrahim b. ‘Umar al-Biqa’i has various style of interpretation. One of them is the maqasid pattern. Study of maqasid patterns in the book Nazm al-Durar fi Tanasib al-‘Ayat wa al-Suwar through several methods carried out by al-Biqa’i. Therefore, this article will review the method used by al-Biqa’i with maqasid style in his interpretation. This research uses qualitative research methods with library research data collection techniques. There are two sources used, namely primary sources which use the books Nazm al-Durar fi Tanasib al-‘Ayat wa al-Suwar and secondary sourceswhich use books and journal related to the topic of discussion. This research found that al-Biqa’i used munasabah science in explaning his maqasid in the Qur’an. This shows that in his interpretation, al-Biqa’i has included each maqasid in his surah and studied them using the munasabah method. Apart from the maqa>sid of each surah found, there are also advantages of each surah. The two are interrelated because the priority of each surah is in accordance with the purpose of the surah (maqa>sid of surah). Keywords : Maqasid Tafsir Style, Book Nazm al-Durar fi Tanasib al-‘Ayat wa al-Suwar, al-Biqa’i